Optimal inkalvningsålder för rekryteringskvigor till mjölkproduktion - Nilsson, Rebecca (2009)
Heifer’s growth may be divided into three main phases: calf period, puberty and pregnancy. When the heifers are about three months old a critical period begins. This period ends when the heifer reach puberty and have her first oestrus at around 9-12 months of age. In the critical period the mammary gland starts to grow at a fast rate and Insulin-like growth factor-1 (IGF-1) transport the growth signals to the mammary glands. If the heifer is reared at extremely high growth rates (>800 g/day) during the critical period the milk yield in future lactations will be negatively affected. A heifer’s future milk yield is determined by many factors during growth and the most important for milk production is calving age and body weight at calving. Results have shown that the milk yield increase significantly in the first lactations with increasing age at calving. Contrary, the heifer begins to be profitable after calving, and thus a low age at calving is desirable for economic reasons. The optimal age at calving has been discussed in the present literature review in which high and low calving ages both have advantages and disadvantages. Data was collected from 110 Swedish Holstein heifers, where results have shown that milk yield in the first lactation increases with increased calving age. The results also shown that the heifers age at calving distinguish between the different months of the year.